Assessment of patient safety and the efficiency of facility utilization following simplified ultra-rapid intravenous infusion of hepatitis B immunoglobulin in a high-volume liver transplantation center - Jeong, I-Ji (Ann Hepatobiliary Pancreat Surg, 2019)
BACKGROUNDS/AIMS: This study intended to evaluate patient safety and efficiency of facility utilization following simplified ultra-rapid intravenous infusion of hepatitis B immunoglobulin (HBIG) in recipients of hepatitis B virus-associated adult liver transplantation (LT), who visited our outpatient clinic. METHODS: Our simplified ultra-rapid infusion protocol was to directly infuse 50 ml volume of 10,000 IU HBIG for 20–25 minutes on an ambulatory basis. The incidence of adverse side-effects and the efficiency of facility utilization were assessed retrospectively. RESULTS: A total of 1,513 patients received 12,472 sessions of HBIG infusion according to simplified ultra-rapid infusion method. Of these, 1,172 patients were converted from conventional ultra-rapid infusion method, and received 8,352 sessions of HBIG infusion for 18 months (mean 7.1 times; 4.8 times per year). The remaining 341 de novo patients received 4,120 sessions of HBIG infusion for 18 months (mean 12.1 times; 8.1 times per year). None of these patients experienced any adverse side-effects following the simplified ultra-rapid infusion. The maximal capacity of HBIG infusion sessions at the injection facility of our outpatient clinic was increased from 65–70 sessions to 80 sessions, after introduction of simplified ultra-rapid infusion method. Mean trough anti-HBs titer was lower, and mean interval of HBIG infusion was longer in the combination therapy group compared with HBIG monotherapy group. CONCLUSIONS: Our high-volume study indicates that in nearly all LT recipients, rapid infusion of highly purified HBIG within 30 minutes was well-tolerated. This suggests that it would be reasonable to perform simplified ultra-rapid infusion protocol widely for patient convenience.